ASSESSMENT OF KNOWLEDGE ABOUT CARDIOPULMONARY RESUSCITATION AMONG SECONDARY MEDICAL SCHOOL STUDENTS - Požar, Hajnalka F; Požar, Čaba F (PONS - medicinski časopis, 2017)
Introduction. Mastering the skills of cardio-pulmonary resuscitation is a basic task for all health workers. In this concept, this paper examines and assesses the knowledge of resuscitation in students of the healthcare professions. Method. The study was conducted as a cross-sectional study among students of the secondary medical school in Novi Sad (n 80), in 2015/16 years. A questionnaire is in the form of a test of knowledge. For statistical analysis we used SPSS program, we used methods of descriptive statistics. For testing statistical significance by sex and age we used the method of cross tables and Pearson’s χ2 test at a confidence level of p ≤ 0.05%. Results. Half of the respondents believe that they do not have enough practical experience to participate in resuscitation. Also, we found a deficit of knowledge in the ratio of air insufflation and external compression of the heart, in the field of medicines and EKG tests. Conclusion. Almost a third of future health workers does not have adequate knowledge of resuscitation, and does not know properly implement the revival. These data confirm the hypothesis that the during the education of future health workers we need to put more emphasis on the management of emergency situations as well as routine drills and practice the procedure of resuscitation.